Impacts of Business Informality on the Creation and Sustainability of MSMEs in Bolivia (2024)
Business informality in the Bolivian context translates into high rates of poverty and vulnerability for those who work in the formal sector, with direct impacts, not only on them, but also on the State's tax collection. This research aimed to address the impacts generated by business informality on the creation and business sustainability of MSMEs in Bolivia and was descriptive in nature, with a mixed approach and methods, techniques, and instruments appropriate to these characteristics were used. A literary review was carried out and a survey was applied to 146 company managers in the following sectors: industrial, commercial and services in the 4 most representative cities of the country (Santa Cruz, La Paz, Cochabamba, and Tarija). The factors with the greatest impact revealed were: the loss of market due to unfair competition, high production costs due to taxes and the workload involved in working formally. On the other hand, informality expands due to the flow of smuggling as a refuge for unemployment, creating a vicious cycle that expands the informal business fabric, placing the country in the first place of informality in Latin America.  JEL Codes: H3, E62 Received: 07/09/2023.  Accepted: 17/12/2023.  Published: 23/01/2024.